Mutant CTNNB1 and histological heterogeneity define metabolic subtypes of hepatoblastoma. Issue 11 (19th September 2017) - Crippa, Stefania; Ancey, Pierre‐Benoit; Vazquez, Jessica; Angelino, Paolo; Rougemont, Anne‐Laure; Guettier, Catherine; Zoete, Vincent; Delorenzi, Mauro; Michielin, Olivier; Meylan, Etienne
Abstract: Hepatoblastoma is the most common malignant pediatric liver cancer. Histological evaluation of tumor biopsies is used to distinguish among the different subtypes of hepatoblastoma, with fetal and embryonal representing the two main epithelial components. With frequent CTNNB1 mutations, hepatoblastoma is a Wnt/β‐catenin‐driven malignancy. Considering that Wnt activation has been associated with tumor metabolic reprogramming, we characterized the metabolic profile of cells from hepatoblastoma and compared it to cells from hepatocellular carcinoma. First, we demonstrated that glucose transporter GLUT3 is a direct TCF4/β‐catenin target gene. RNA sequencing enabled to identify molecular and metabolic features specific to hepatoblastoma and revealed that several glycolytic enzymes are overexpressed in embryonal‐like compared to fetal‐like tumor cells. This led us to implement successfully three biomarkers to distinguish embryonal from fetal components by immunohistochemistry from a large panel of human hepatoblastoma samples. Functional analyses demonstrated that embryonal‐like hepatoblastoma cells are highly glycolytic and sensitive to hexokinase‐1 silencing. Altogether, our findings reveal a new, metabolic classification of human hepatoblastoma, with potential future implications for patients' diagnosis and treatment. Synopsis: The fetal and embryonal subtypes of hepatoblastoma (HB), a rare pediatric liver cancer, are shown to represent two distinct metabolic subtypes, potentially offering new avenues for diagnosis or treatment of this malignancy. RNA sequencing from human liver tumor cell lines highlights signatures of carbohydrate transport and metabolism in HB cells compared to cells from hepatocellular carcinoma. HB subtype analyses demonstrate that embryonal‐like HB cells display enhanced glycolysis, whereas fetal‐like HB cells have stronger capacity for β‐oxidation of fatty acids. Glucose transporter GLUT3 is a Wnt/β‐catenin target gene whose protein product, strongly expressed in embryonal‐like HB cells, drives glucose uptake and glycolysis. Glycolysis‐associated proteins GLUT3 and LDHB are detected in 38 and 86% of HB tumor cases with embryonal components, but only in 0 and 46% of pure fetal HBs. Gluconeogenesis‐ and glycogenolysis‐associated protein G6PC is detected in 30% of HB tumor cases with embryonal components, and in 93% of pure fetal HB cases. Abstract : The fetal and embryonal subtypes of hepatoblastoma (HB), a rare pediatric liver cancer, are shown to represent two distinct metabolic subtypes, potentially offering new avenues for diagnosis or treatment of this malignancy.